PROFESSIONLLY-APPLIED PHISICAL TRAINING OF MSTU CA - V. I. Shalupin; I. A. Pismenskiy (Научный вестник МГТУ ГА, 2016)
Discusses issues of model characteristics of the engineering and technical personnel of civil aviation for physical culture. The formation of professional and applied physical training of electricians and radio operators serving aircraft.